Polyazine-supported carbon catalyst and catalytic electrode using the same
A carbon catalyst supporting polyazine compounds addresses the need for resource-efficient and environmentally friendly proton reduction by enhancing electrochemical proton reduction activity, improving energy efficiency in proton reduction reactions.
Patent Information
- Application Number
- JP2020024839
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-02-18
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2040-02-18
AI Technical Summary
Existing electrocatalysts for proton reduction require metal elements, which are resource-intensive and have environmental impacts, and there is a lack of effective nonmetallic catalysts for proton reduction.
A carbon catalyst supporting a polyazine compound, produced through the reaction of a nitrile compound and a base, exhibits high electrochemical proton reduction activity without metal elements, utilizing specific polyazine structures and production methods.
The carbon catalyst enhances the energy efficiency of proton reduction reactions, offering a resource-saving and environmentally friendly solution with improved catalytic performance.
Smart Images

Figure 0007603378000020 
Figure 0007603378000021 
Figure 0007603378000022
Abstract
Description
[Technical field]
[0001] The present invention relates to a carbon catalyst carrying a polyazine compound, which is useful as an electrode material for reducing the overvoltage in an electrochemical proton reduction reaction. [Background technology]
[0002] Polyazine compounds, which are polymers containing triazine rings as repeating units, have a semiconductor-like electronic structure derived from a two-dimensional conjugated system and azine rings that function as catalytic active sites, and are therefore useful as electrode catalysts. Patent Document 1 discloses a method for producing a hybrid material similar to the carbon catalyst of the present invention, which combines a polyazine compound and conductive carbon, and a method for applying the hybrid material as an electrode catalyst material, but the hybrid material needs to be added with a metal element in order to function as an electrode catalyst, and there is no description of the electrode catalytic activity of a material consisting of only a polyazine compound and conductive carbon. In addition, Non-Patent Document 1 describes the application of a polyazine ring compound as an oxygen reduction electrode catalyst, but does not mention the application as a proton reduction electrode catalyst. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] WO2016035321A1 [Patent Document 2] JP2017160144 [Patent Document 3] WO2017050689A1 [Non-patent literature]
[0004] [Non-Patent Document 1] Polymer, 2017, volume 126, pages 283-290 [Non-Patent Document 2] Angewante Chemie International Edition, 2008, Vol. 47, pp. 3450-3453 [Non-Patent Document 3] Inorganic Chemistry, 2008, vol. 47, pp. 4481-4489 Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a highly active proton reduction electrode catalyst which is composed only of non-metallic elements and which is resource-saving and has a low environmental impact. [Means for solving the problem]
[0006] As a result of intensive research aimed at solving the above problems, the present inventors have found that a carbon catalyst supporting a polyazine compound obtained by reacting a nitrile compound with a base has good electrochemical proton reduction activity as a non-metallic catalyst, and have thus completed the present invention.
[0007] That is, the present invention is (i) General formula (1)
[0008] [ka] (wherein X represents a nitrogen atom or CH), and an arylene group represented by the general formula (2):
[0009] [ka] The repeating unit is a triazine ring represented by the general formula (3) at the molecular end.
[0010] [ka] (wherein Ar represents a hydrogen atom or a nitrogen-containing aromatic hydrocarbon group which is a monocyclic, linked, or fused ring group having 4 to 18 carbon atoms. The nitrogen-containing aromatic hydrocarbon group may be modified with an alkyl group or a cyano group having 1 to 6 carbon atoms.) (ii) The carbon catalyst according to (i) above, wherein the nitrogen-containing aromatic hydrocarbon group is a pyridyl group, a bipyridyl group, a pyrimidyl group, a pyrazyl group, a quinolinyl group, a phenanthrolinyl group, a cyanopyridyl group, a dicyanopyridyl group, a carbazolyl group, or a diphenylamino group. (iii) The carbon catalyst according to (i) or (ii) above, wherein Ar is a cyanopyridyl group. (iv) The carbon catalyst according to (i) or (ii) above, wherein Ar is a hydrogen atom. (v) The carbon catalyst according to any one of (i) to (iv) above, wherein the polyazine compound has a thermal decomposition point in the range of 350° C. to 700° C. (vi) The carbon catalyst according to (i) or (ii) above, which supports a polyazine compound having a molecular structure represented by the following formula (I) or (II):
[0011] [ka]
[0012] [ka] (vii) The carbon catalyst according to any one of the above (i) to (vi), wherein the polyazine compound is produced by mixing and heating a nitrile compound and a metal hydroxide salt. (viii) The carbon catalyst according to any one of (i) to (vii) above, wherein the content of the polyazine compound is in the range of 0.01 to 50% by weight based on the weight of carbon. (ix) The carbon catalyst according to any one of (i) to (viii) above, wherein the carbon is at least one selected from the group consisting of acetylene black, furnace black, carbon black, activated carbon, carbon nanotubes, and graphite. This is regarding.
[0013] The present invention also provides (x) A catalytic electrode comprising the carbon catalyst according to any one of (i) to (ix). (xi) A method for producing the catalytic electrode according to (x) above, comprising the following three steps: Step 1: A step of supporting a polyazine compound on carbon to produce a carbon catalyst. Step 2: A step of preparing a catalyst ink consisting of a carbon catalyst, a binder, and a dispersion medium. Step 3: The catalyst ink prepared in step 2 is applied onto a current collector and cured by heating. (xii) A method for producing hydrogen, comprising using the catalytic electrode according to (x) as a proton reducing electrode. (xiii) A fuel cell comprising the catalytic electrode described in (x). This is regarding. Effect of the Invention
[0014] By using the carbon catalyst of the present invention carrying a polyazine compound as a material for forming an electrode, it is possible to improve the energy efficiency of the electrochemical reduction of protons. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present invention will now be described in further detail.
[0016] X in the arylene group (1) contained as a repeating unit in the polyazine compound supported on the carbon catalyst of the present invention represents a nitrogen atom or CH, and X is preferably CH in terms of ease of synthesis. Specific examples of the arylene group (1) include a 2,3-pyridylene group, a 2,4-pyridylene group, a 2,5-pyridylene group, a 2,6-pyridylene group, a 3,4-pyridylene group, a 3,5-pyridylene group, a 2,4-pyrimidylene group, a 2,5-pyrimidylene group, a 4,5-pyrimidylene group, and a 4,6-pyrimidylene group, and 2,4-pyridylene group, 2,5-pyridylene group, 2,6-pyridylene group, and 3,5-pyridylene group are preferred in terms of ease of synthesis, and 2,4-pyridylene group or 2,6-pyridylene group are more preferred in terms of excellent catalytic activity.
[0017] The terminal group (3) contained in the polyazine compound supported on the carbon catalyst of the present invention represents a nitrogen-containing aromatic hydrocarbon group having 4 to 18 carbon atoms and being a single ring, a linked ring, or a condensed ring. Specific examples of the terminal group (3) include a pyrrolyl group, a pyridyl group, a terpyridinyl group, a bipyridyl group, a pyrimidyl group, a pyrazyl group, a quinolinyl group, an isoquinolinyl group, a phenanthrolinyl group, an indolinyl group, a carbazolyl group, a phthalazinyl group, a naphthyridinyl group, a quinoxalinyl group, a quinazolinyl group, an acridinyl group, and the like.
[0018] The nitrogen-containing aromatic hydrocarbon group may be substituted with an alkyl group having 1 to 6 carbon atoms. The alkyl group may be any of linear, branched, and cyclic alkyl groups, and specific examples thereof include a methyl group, a cyclohexylmethyl group, an ethyl group, a 2-cyclopentylethyl group, a propyl group, a 2,2-dimethylpropyl group, a 3-cyclopropylpropyl group, a 1-methylethyl group, a cyclopropyl group, a butyl group, a 2-methylbutyl group, a 3-methylbutyl group, a 2-butyl group, a 3-methylbutan-2-yl group, a tert-butyl group, a cyclobutyl group, a pentyl group, a 2-methylpentyl group, a 2-pentyl group, a 2-methylpentan-2-yl group, a 3-pentyl group, a cyclopentyl group, a 2-methylcyclopentyl group, a 3-methylcyclopentyl group, a hexyl group, a 2-hexyl group, a 3-hexyl group, and a cyclohexyl group.
[0019] As the terminal group (3), a nitrogen-containing aromatic hydrocarbon group having 5 to 10 carbon atoms and a cyano group is preferred, from the viewpoint of ease of synthesis of a high molecular weight molecule, and a cyanopyridyl group or a dicyanopyridyl group is more preferred.
[0020] The terminal group (3) is preferably a hydrogen atom.
[0021] The polyazine compound supported on the carbon catalyst of the present invention has a thermal decomposition point preferably in the range of 200°C to 700°C, more preferably in the range of 300°C to 700°C, and particularly preferably in the range of 300°C to 600°C, in view of its excellent thermal stability.
[0022] The polyazine compound supported on the carbon catalyst of the present invention preferably has a structure represented by the following formula (I) or (II).
[0023] [ka]
[0024] [ka] Specific examples of the polyazine compound supported on the carbon catalyst of the present invention include the compounds (I) to (II) and the following (A-1) to (A-36), but the present invention is not limited to these.
[0025] [ka]
[0026] [ka]
[0027] [ka] As the polyazine compound supported on the carbon catalyst of the present invention, the compounds represented by (I), (II), (A-3), (A-4) and (A-28) are preferred because of their good catalytic activity.
[0028] The polyazine compound supported on the carbon catalyst of the present invention can be produced by a nucleophilic substitution reaction with a Grignard reagent (for example, the reaction disclosed in Patent Document 2), a cross-coupling reaction (for example, the reaction disclosed in Non-Patent Document 1), a triazine ring formation reaction by trimerization of a nitrile compound, etc., but the triazine ring formation reaction is preferred in terms of the ease of reaction operation. As the triazine ring formation reaction, a method of mixing and heating a nitrile compound with a zinc chloride melt (for example, the method disclosed in Non-Patent Document 2), a method of mixing and heating a strong acid (for example, the method disclosed in Non-Patent Document 1), a method of mixing and heating a base (for example, the method disclosed in Non-Patent Document 3), etc. are known, but the method of mixing and heating a nitrile compound with a base is preferred in terms of high yield. In this case, the nitrile compound used can be produced by a method well known to those skilled in the art. In addition, a commercially available product may be used.
[0029] The base used in the method of mixing and heating a nitrile compound and a base may be either an inorganic base or an organic base, and examples thereof include metal hydroxides such as sodium hydroxide, potassium hydroxide, cesium hydroxide, magnesium hydroxide, calcium hydroxide, and barium hydroxide; metal carbonates such as sodium carbonate, potassium carbonate, lithium carbonate, and cesium carbonate; metal acetates such as potassium acetate and sodium acetate; metal phosphates such as potassium phosphate and sodium phosphate; metal fluoride salts such as sodium fluoride, potassium fluoride, and cesium fluoride; metal alkoxides such as sodium methoxide, potassium methoxide, sodium ethoxide, potassium isopropyl oxide, and potassium tert-butoxide; triethylamine; Examples of suitable bases include amines such as diisopropylethylamine, tributylamine, N-methylpyrrolidine, N-methylpiperidine, N,N'-dimethylpiperazine, N-methylmorpholine, 1,4-diazabicyclo[2.2.2]octane, 1,8-diazabicyclo[5.4.0]-7-undecene, N,N-dimethylaniline, N,N-diethylaniline, N,N-diethyltoluidine, pyridine, and picoline, and metal amides such as lithium amide, sodium amide, potassium amide, lithium diisopropylamide, sodium diisopropylamide, lithium bis(trimethylsilyl)amide, sodium bis(trimethylsilyl)amide, and potassium bis(trimethylsilyl)amide. Among these, inorganic bases are preferred in that they are easily purified, metal hydroxides are more preferred in that they provide a good yield, and sodium hydroxide is particularly preferred in that it is inexpensive.
[0030] In the method of mixing a nitrile compound and a base and heating the mixture, the molar equivalent of the base to be used relative to the nitrile compound is preferably in the range of 0.001 to 0.8 molar equivalents, and more preferably in the range of 0.02 to 0.20 molar equivalents in terms of good yield. In the method of mixing and heating a nitrile compound and a base, a crown ether may be added for the purpose of improving the reaction yield. Examples of crown ethers include 1,4,7-trioxacyclonane, 1,4,7,10-tetraoxacyclododecane, 1,4,7,10,13-pentaoxacyclopentadecane, 1,4,7,10,13,16-hexaoxacyclooctadecane, and 1,4,7,10,13,16,19,22-octaoxacyclotetracosane. When the base is a metal hydroxide, a crown ether that matches the ionic radius of the metal ion may be appropriately selected and used. The amount of crown ether used is preferably in the range of 1 to 2 equivalents relative to the base.
[0031] In the method of mixing a nitrile compound and a base and heating them, the heating temperature is preferably selected appropriately from the range of 100 to 400°C, more preferably 150 to 300°C, in terms of good yield.
[0032] Next, a method for producing the carbon catalyst of the present invention and a catalyst electrode containing the carbon catalyst of the present invention (hereinafter sometimes referred to as the electrode of the present invention) will be described.
[0033] The carbon catalyst of the present invention and the electrode of the present invention can be obtained through the following three steps. Step 1: A step of supporting a polyazine compound on carbon to produce a carbon catalyst. Step 2: A step of preparing a catalyst ink consisting of a carbon catalyst, a binder, and a dispersion medium. Step 3: The catalyst ink prepared in step 2 is applied onto a current collector and cured by heating.
[0034] Step 1 is a step of producing the carbon catalyst of the present invention by dispersing or dissolving a polyazine compound and carbon in an organic solvent, and then removing the organic solvent.
[0035] Examples of the carbon used in step 1 include acetylene black, furnace black, carbon black, activated carbon, carbon nanotubes, graphite, etc., and two or more types of carbon can be used in combination. The carbon is more preferably acetylene black in terms of high catalytic activity. The polyazine compound used in step 1 is preferably in the range of 0.005% by weight to 99% by weight relative to carbon in terms of high material conductivity, and more preferably in the range of 0.01% by weight to 50% by weight in terms of high catalytic activity.
[0036] The organic solvent used in step 1 is not particularly limited, and examples thereof include monoalcohols such as methanol, ethanol, propanol, butanol, hexanol, and cyclohexanol; ethers such as 2-methoxyethanol, 2-ethoxyethanol, 2-butoxyethanol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethyl ether, diisopropyl ether, dibutyl ether, cyclopentyl methyl ether (CPME), tetrahydrofuran (THF), 2-methyltetrahydrofuran, 1,4-dioxane, and dimethoxyethane; aromatic hydrocarbons such as benzene, toluene, xylene, mesitylene, nitrobenzene, tetralin, and anisole; dichloromethane, chloroform, 1,2-dichloroethane, and the like; Examples of the solvent include halogenated hydrocarbons such as chloroethane, 1,1,2,2-tetrachloroethane, dichlorobenzene, chlorobenzene, trichlorobenzene, and 1-chloronaphthalene, carbonates such as ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and 4-fluoroethylene carbonate, esters such as methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, butyl acetate, methyl propionate, ethyl propionate, methyl butyrate, and γ-lactone, and amides such as N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), and N-methylpyrrolidone (NMP), and these may be mixed in any ratio.Toluene, chloroform, DMF, and NMP are preferred in terms of the solubility or dispersibility of polyazine compounds, and chloroform or DMF is more preferred in terms of easy removal. There is no particular limitation on the amount of organic solvent used, and the amount can be selected appropriately so that the content of the polyazine compound in the dispersion liquid is preferably 0.01 to 90% by weight, more preferably 0.1 to 50% by weight.
[0037] In order to improve the activity of the catalyst, an additive may be added in step 1. The additive is a complex or salt containing an element of Groups 3 to 12, and specific examples thereof include complexes or salts of manganese, iron, cobalt, nickel, copper, zinc, molybdenum, ruthenium, rhodium, palladium, silver, platinum, gold, etc.
[0038] In step 1, the method for dissolving or dispersing the polyazine compound etc. in the organic solvent is not limited, and for example, methods well known to those skilled in the art such as heating and stirring, shaking, ball milling, ultrasonic irradiation, etc. can be used. Heating and stirring or ultrasonic irradiation are preferred because they provide good dispersibility of the polyazine compound etc.
[0039] The carbon catalyst of the present invention can be obtained by removing the organic solvent by filtration, centrifugation, etc., after the completion of the dissolving or dispersing operation. The obtained carbon catalyst may be dried by heating at a temperature appropriately selected from the range of 60° C. to 450° C. as necessary, and it is preferable to carry out the heat treatment at 200 to 400° C. in terms of improving the catalytic activity.
[0040] Step 2 is a step of dispersing the carbon catalyst of the present invention and a binder in a dispersion medium to prepare a catalyst ink to be used in manufacturing the electrode of the present invention (hereinafter, may be referred to as the catalyst ink of the present invention). For example, the method disclosed in Patent Document 2 can be used.
[0041] The binder used in step 2 may be any material that has the function of binding the carbon catalyst and the current collector, and examples thereof include hydrophobic resins such as polytetrafluoroethylene and polyvinylidene fluoride, hydrophilic resins such as cellulose fiber, polyvinyl alcohol, and polyethylene glycol, and cation exchange resins such as Amberlite (manufactured by Organo Corporation), Nafion (manufactured by DuPont), and Lewatit (manufactured by Lanxess), among which cation exchange resins are preferred and Nafion is more preferred in terms of excellent proton conductivity. There are no particular limitations on the amount of binder used, and an amount that results in a binder content in the catalyst ink appropriately selected from preferably 0.01 to 20% by weight, and more preferably 0.01 to 10% by weight, can be used.
[0042] The dispersion medium used in step 2 may be water, an organic solvent, a polymer dispersion medium, or the like, and an organic solvent is preferred in terms of good dispersibility. Specific examples of the organic solvent include monoalcohols such as methanol, ethanol, propanol, butanol, hexanol, and cyclohexanol, ethers such as 2-methoxyethanol, 2-ethoxyethanol, 2-butoxyethanol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethyl ether, diisopropyl ether, dibutyl ether, cyclopentyl methyl ether (CPME), tetrahydrofuran (THF), 2-methyltetrahydrofuran, 1,4-dioxane, and dimethoxyethane, aromatic hydrocarbons such as benzene, toluene, xylene, mesitylene, nitrobenzene, tetralin, and anisole, dichloromethane, chloroform, 1,2-dichloroethane, and the like. Examples of the solvent include halogenated hydrocarbons such as ethane, 1,1,2,2-tetrachloroethane, dichlorobenzene, chlorobenzene, trichlorobenzene, and 1-chloronaphthalene, carbonates such as ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and 4-fluoroethylene carbonate, esters such as methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, butyl acetate, methyl propionate, ethyl propionate, methyl butyrate, and γ-lactone, and amides such as N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), and N-methylpyrrolidone (NMP), which may be mixed in any ratio. In terms of good dispersibility of the binder, water and monoalcohols are preferred, and water, methanol, ethanol, propanol, butanol, or a mixed solvent thereof are more preferred, and methanol or ethanol is particularly preferred in terms of ease of removal. There is no particular limitation on the amount of the dispersion medium used, and the amount can be selected appropriately so that the content of the polyazine compound in the dispersion liquid is preferably 0.01 to 90% by weight, more preferably 0.1 to 50% by weight.
[0043] In step 2, the method for dispersing the carbon catalyst of the present invention in the dispersion medium can be the same as the method exemplified in step 1, and ultrasonic irradiation is preferred in terms of good dispersibility. The dispersion obtained after the dispersion operation can be used as a catalyst ink in the next step.
[0044] Step 3 is a step in which the catalyst ink of the present invention is applied to a current collector and then heated and cured to obtain the electrode of the present invention. Examples of the current collector used in step 3 include precious metals such as platinum, gold, silver, rhodium, and ruthenium, base metals such as stainless steel, iron, aluminum, copper, and titanium, and carbon materials such as glassy carbon and carbon nonwoven fabric. Among these, precious metals and carbon materials are preferred from the viewpoints of low cost and high acid resistance, and glassy carbon is more preferred.
[0045] In step 3, the method for applying the catalyst ink of the present invention to the current collector can be a method generally used in a wet thin film production process. Specific examples include cast coating, spin coating, dip coating, spray coating, flow coating, roll coating, curtain coating, bar coating, ultrasonic coating, screen printing, brush coating, sponge coating, and the like. Cast coating, spin coating, dip coating, and spray coating are preferred in that they are inexpensive and can produce a smooth film, and cast coating is more preferred in that they are simple.
[0046] The heat curing temperature in step 3 may be any temperature at which the dispersion medium volatilizes from the coating of the catalyst ink of the present invention and a catalyst layer made of dispersoid is formed, and heating is preferably performed at a temperature appropriately selected from the range of 40 to 400°C, preferably 50 to 250°C in terms of being able to suppress thermal decomposition of the catalyst.
[0047] The heat curing time in step 3 may be any time that allows the dispersion medium to volatilize from the coating of the catalyst ink of the present invention and a catalyst layer made of dispersoid to be formed, and it is preferable to carry out the baking for a time appropriately selected from the range of preferably 1 minute to 5 hours, more preferably 5 to 30 minutes.
[0048] After step 3 is completed, steps 2 and 3 may be repeated to obtain a catalyst film of a desired thickness. The carbon catalyst of the present invention has a low proton reduction overpotential for a nonmetallic material, and can therefore be used as a resource-saving proton reduction catalyst electrode. The carbon catalyst of the present invention can efficiently electrolyze water while saving resources, and therefore has the potential for application in the field of energy conversion.
[0049] When the carbon catalyst of the present invention is used as an electrode catalyst for a hydrogen production device, the current collector, conductive assistant, and binder in the electrode may be made of materials known in the art depending on the type of electrolyte used and the electrolysis conditions. In addition, the electrode may be made by a method commonly used in the art.
[0050] When the carbon catalyst of the present invention is used as a hydrogen electrode of a fuel cell, the current collector, conductive assistant, and binder in the electrode may be made of materials known in the art depending on the type of electrolyte used and the operating conditions. In addition, the electrode may be made by a method commonly used in the art. EXAMPLES
[0051] The present invention will be described in more detail below with reference to examples, comparative examples and reference examples, but the present invention should not be construed as being limited to these. [ 1 H-NMR measurement] 1 For H-NMR measurements, a Bruker ASCEND HD (400 MHz; manufactured by BRUKER) was used. 1H-NMR was measured using deuterated chloroform (CDCl3) as the measurement solvent and tetramethylsilane (TMS) as the internal standard. Commercially available reagents were used. [Infrared spectroscopy] The infrared spectrum was measured by the ATR method using a powdered compound and a Fourier transform infrared spectrometer (HORIBA, FT-720). -1 From 4000cm -1 The spectra were measured in the range of [TG / DTA measurement] The thermal decomposition temperature was measured by thermogravimetric analysis in a dry air atmosphere using a thermogravimetric analyzer (Hitachi High-Technologies, TG / DTA-6200). Using powdered compounds (approximately 5 mg), the temperature range was from 30°C to 800°C, and the heating rate was 10°C min -1 Measurements were performed. [Proton reduction activity evaluation] The activity of the proton reduction reaction was evaluated by linear sweep voltammetry using a potentiostat (Hokuto Denko, HSV-100). The working electrode was a glassy carbon electrode (GC electrode) with an electrode catalyst layer formed on its surface, the reference electrode was a silver-silver chloride electrode with a saturated potassium chloride solution as the internal solution, the counter electrode was a Pt wire, and the electrolyte was 0.5 mol cm -3 The sulfuric acid solution was used. The sweep range was 0 V to -1.2 V (vs. Ag / AgCl), and the potential sweep rate was 50 mV / sec. -1 The measurements were carried out as follows. From the plot of the potential and proton reduction current obtained, -0.2 mA cm -2 Achieved potential (Onset,[Vvs.SHE]), -5mAcm -2 Achieved potential (E 5mA ,[Vvs.SHE]), Tafel slope(TS,[mVdecade -1 ]) was calculated. Reference example-1
[0052] [ka] 2-Cyanopyrimidine (200 mg, 1.6 mmol) and sodium hydroxide (7.8 mg, 0.20 mmol) were ground and mixed. Under an argon atmosphere, this mixture was heated and stirred at 220°C for 4 hours. After the reaction was completed, the product was washed with water and methanol and then purified by silica gel chromatography to obtain the desired 2,4,6-tri(2-pyrimidyl)-1,3,5-triazine (A-4) (120 mg, 0.38 mmol, 11%). 1 HNMR(CDCl3): δ7.54(t,J=4.9Hz,3H),9.13(dd,J=4.9Hz,0.7Hz,6H). Reference example-2
[0053] [ka] 6-Cyano-2,2'-bipyridyl (50mg, 0.28mmol) and sodium hydroxide (2.3mg, 0.06mmol) were ground and mixed. Under an argon atmosphere, this mixture was heated and stirred at 220°C for 4 hours. After the reaction was completed, the product was washed with water and methanol to obtain the desired 2,4,6-tri(2-pyrimidyl)-1,3,5-triazine (A-28) (33mg, 0.06mmol, 66%). 1 HNMR(CDCl3): δ7.37(m,3H),7.86(m,3H),8.01 (t,3H),8.25(dd,J=7.7,1.1Hz,3H),8.40(m,3H),8.62 (dd,J=7.7,1.1Hz,3H),8.70(m,3H). Reference example-3
[0054] [ka] Potassium hydroxide (1 mg, 0.02 mmol), 1,4,7,10,13,16-hexaoxacyclooctadecane (5.3 mg, 0.02 mmol), and ethanol (1 mL) were placed in a reaction vessel and stirred at room temperature for 20 minutes to obtain a homogeneous solution, after which the ethanol was removed under reduced pressure. 2,4-dicyanopyridine (200 mg, 0.15 mmol) was added to the reaction vessel and heated and stirred at 300°C for 4 hours under an argon atmosphere. After the reaction was completed, the product was washed with chloroform and pure water to obtain a white solid product (82 mg). After crushing the product, the infrared spectrum was measured (Figure 1). -1 Since an absorption peak [a1] derived from the triazine ring appeared in the vicinity, it was confirmed that this was the target polyazine compound (I).
[0055] The thermal decomposition temperature of compound (I) was approximately 400°C (Figure 3). Reference example-4
[0056] [ka] 2,4-dicyanopyridine (200 mg, 1.55 mmol) and sodium hydroxide (13 mg, 0.32 mmol) were ground and mixed. Under an argon atmosphere, this mixture was heated and stirred at 220° C. for 4 hours. After the reaction was completed, the product was washed with chloroform and pure water to obtain a brown solid product (152 mg, 76%). After crushing the product, the infrared spectrum was measured (Figure 3), revealing a wavenumber of 1580 cm -1 Since an absorption peak [a1] derived from the triazine ring appeared in the vicinity, it was confirmed that it was the target polyazine compound (II).
[0057] The thermal decomposition temperature of compound (II) was approximately 600°C (Figure 4). Example 1 Carbon catalyst production Compound (A-3) (1 mg) and acetylene black (Denka, Li-100, 5 mg) were added to chloroform (1 mL) and then ultrasonically dispersed. The dispersed matter was filtered and then vacuum dried to obtain a carbon catalyst supporting compound (A-3) (5 mg). Preparation of catalyst ink A carbon catalyst (5 mg) supporting compound (A-3) and a Nafion dispersion (50 μL) were suspended in ethanol (950 μL) and ultrasonically dispersed to prepare a catalyst ink. Preparation of electrodes containing carbon catalysts This catalyst ink (6 μL) was cast onto the GC electrode and then dried at 60° C. to form an electrode catalyst layer on the GC electrode. Proton reduction activity evaluation The proton reduction catalytic activity measured by linear sweep voltammetry (Figure 7) of the GC electrode on which the electrode catalyst layer was formed is shown in Table 1. Example 2 A carbon catalyst was produced using the compound (A-4) instead of the compound (A-3) according to the method described in Example 1. The proton reduction catalytic activity is shown in Table 1 and FIG. Example 3 A carbon catalyst was produced using compound (A-28) instead of compound (A-3) according to the method described in Example 1. The proton reduction catalytic activity is shown in Table 1 and FIG. Example 4 According to the method described in Example-1, a carbon catalyst was produced using compound (I) instead of compound (A-3). When the infrared spectrum was measured, the support of the polyazine compound was confirmed (FIG. 5). The proton reduction catalytic activity is shown in Table 1 and FIG. 8. Example 5 According to the method described in Example-1, a carbon catalyst was produced using compound (II) instead of compound (A-3). When the infrared spectrum was measured, the support of the polyazine compound was confirmed (FIG. 6). The proton reduction catalytic activity is shown in Table 1 and FIG. 8. Comparative Example 1 Acetylene black (Denka, Li-100) was used instead of the carbon catalyst in accordance with the method described in Example 1. The proton reduction catalytic activity is shown in Table 1 and FIG. Comparative Example 2 A carbon catalyst was produced according to the method described in Example 1, and then annealed for 4 hours at 200° C. The proton reduction catalytic activity is shown in Table 1. Comparative Example 3 Comparison with previous cases
[0058] [ka] Under an argon atmosphere, trifluoromethanesulfonic acid (1.70 g, 11.3 mmol) was added to a reaction vessel, which was then heated to 100° C. While heating and stirring, a dichloromethane solution (20 mL) of 1,4-dicyanobenzene (200 mg, 0.15 mmol) was added dropwise over 2 hours. After the addition was complete, the mixture was heated and stirred at 100° C. for 4 hours, and then ethanol (100 mL) was added to the reaction vessel. The resulting precipitate was collected by filtration and washed with ethanol and DMF to obtain compound (C) (124 mg, 62%). A carbon catalyst was produced using compound (C) instead of compound (A-3) according to the method described in Example 1. The proton reduction catalytic activity is shown in Table 1 and FIG.
[0059] [Table 1] In Examples 1 to 5 and Comparative Example 1, the proton reduction activity of carbon catalysts carrying various polyazine compounds was compared with the catalytic activity of unsupported carbon. 5mA It was found that the carbon catalysts carrying the polyazine compound (Examples 1 to 5) had catalytic activity for the proton reduction reaction. 5mA This indicates that the carbon catalyst carrying the polyazine compound (II) (Example 5) has catalytic activity for the proton reduction reaction even in the high current region. In Example 1 and Comparative Example 2, the presence or absence of heat treatment was compared for the carbon catalyst supporting the compound (A-3). Heat treatment of the carbon catalyst increased the onset. It was found that heat treatment improves the proton reduction activity. This is believed to be due to the effect of annealing at high temperature for a long period of time, which reduced the interfacial resistance between the carbon support and the polyazine compound. In Example 5 and Comparative Example 3, the carbon catalyst supporting the polyazine compound (C) reported in Non-Patent Document 1 was compared with the carbon catalyst of the present invention. The carbon catalyst supporting the polyazine compound (II) had a higher Onset, E 5mA Since both of these values are high, it was found that the electrode carrying the carbon catalyst of the present invention has better proton reduction catalytic activity than the known triazine-containing polymer material. [Brief description of the drawings]
[0060] [Figure 1] 1 is an infrared spectrum of polyazine compound (I). [Diagram 2] 1 is a thermogravimetric curve of polyazine compound (I) in an air atmosphere. [Diagram 3] 1 is an infrared spectrum of a polyazine compound (II). [Figure 4] 1 is a thermogravimetric curve of polyazine compound (II) in an air atmosphere. [Diagram 5] 1 shows infrared spectra of a carbon support, a polyazine compound (I), and a carbon catalyst supporting the polyazine compound (I). [Figure 6] 1 shows infrared spectra of a carbon support, a polyazine compound (II), and a carbon catalyst supporting the polyazine compound (II). [Figure 7] 1 shows linear sweep voltammograms corresponding to the proton reduction reaction of the catalytic electrodes described in Examples 1, 2, and 3 and Comparative Example 1. [Figure 8] 1 shows linear sweep voltammograms corresponding to a proton reduction reaction of the catalytic electrodes described in Example 4, Example 5, Comparative Example 1, and Comparative Example 3.
Claims
1. The following formulas (A-1) to (A-36) 【Chemistry 1】 【Chemistry 2】 【Chemistry 3】 A proton reduction electrode catalyst comprising a carbon-supported polyazine compound represented by the following formula:
2. 2. The proton reduction electrode catalyst according to claim 1, wherein the carbon is at least one type selected from the group consisting of acetylene black, furnace black, carbon black, activated carbon, carbon nanotubes, and graphite.
3. A method for producing a proton reduction electrode having the proton reduction electrode catalyst according to claim 1, comprising the following three steps: Step 1: A step of supporting any one of the polyazine compounds represented by the formulae (A-1) to (A-36) on carbon to produce a proton reduction electrode catalyst. Step 2: A step of preparing a catalyst ink comprising a proton reduction electrode catalyst, a binder, and a dispersion medium. Step 3: A step of applying the catalyst ink prepared in step 2 onto a current collector and curing it by heating.
4. A fuel cell comprising a proton reduction electrode having the proton reduction electrode catalyst according to claim 1.
Citation Information
Patent Citations
Non-noble metal-nitrogen-carbon oxygen reduction catalyst and preparation method thereof
CN105047953A
4,6-dichlorotriazine compound and method of producing the same
JP2017160144A
Conductive hybrid material including covalent organic structure
WO2016035321A1
Method for producing a layered (semi-)conductive material
WO2017050689A1
